Radiographic structural findings in mandibular condyle of orthodontically treated young patients, a possibility of an iatrogenic temporomandibular joint involvement - Arati Panchbhai; Rahul Bhowate (Wolters Kluwer Medknow Publications, 2016)
Aim: Temporomandibular disorders joint disorders (TMD) are commonly seen in population. There can be varied etiology to this. The purpose of the study was to study the possible association between orthodontic treatment and TMD. Materials and Methods: For the present study, the 720 subjects were assessed in 2 groups as orthodontically treated group (370) and control group without malocclusion (350). The structural findings were assessed as per the criteria. The data were subjected to statistical analysis using Chi-square test and Pearson's correlation. Results: For all the intergroup and intragroup, the findings were insignificant. Though insignificantly, marginal erosion was common finding followed by flattening and rarefaction. Conclusion: Overall, the study could not confirm the association that orthodontic treatment may lead to TMD. The next extensive study needs to be conducted considering clinical signs and symptoms and the long-term follow-ups.